An Ap Star Catalog Based on LAMOST DR9 - Fangfei Shi; Huawei Zhang; Jianning Fu; Donald Kurtz; Maosheng Xiang (The Astrophysical Journal, 2023)
We present a sample of 2700 Ap stars in the Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST) DR9 catalog. The candidates are first selected to be in a temperature range typical of Ap stars by using the BP − RP color index from Gaia DR3. Then the 5200 Å flux depression features characteristic of Ap stars are visually checked in LAMOST DR9 spectra. The detailed spectral features are given by applying a modified spectral classification program, MKCLASS. The stellar parameters of these Ap stars, such as the T _eff , $logg$ , [Fe/H], [Si/H], and $v\sin i$ , are either extracted from a hot star catalog or derived through empirical relations and then a statistical analysis is carried out. The evolutionary stages are also discussed. Finally, we discuss the rotation and pulsation features of those that have TESS or Kepler light curves. Among these Ap stars, we find seven new rotation variables, one new roAp star, and a new δ Scuti pulsation of a previously known roAp star.